O estupro como violência de gênero - Placca, Caroline Lopes (2018)
The current dissertation has as its main goal the investigation regarding how gender influences the reality of rape in Brazil. Therefore, we used the deductive and the criticalanalytical methods, as well as primary and secondary sources and jurisprudence regarding the matter. Firstly we studied some concepts of the feminist theory, presented by authors Heleieth Saffioti, Susan Brownmiller and Catharine Mackinnon, who helped with the comprehension of gender constructions about women and its incidence in relation to rape. We then analyzed the international legislation's evolution that reverberated within the internal order, as well as studied the evolution of rape crime in the national legislation, always focusing on a gender perspective. Then, we set out to observe data on the Brazilian society, emphasizing the social impressions on rape and gender, as well as analyzing the number of notifications of rape in the country and the main characteristics of the people involved in the crime. We finalized the analysis with Precedent 608 issued by the Federal Supreme Court (STF), with the case of Inês Etienne, two matters of the legal world that help with the comprehension of how essential it is to discuss gender in order to avoid violations to women's rights. We verified that gender is directly related to rape, building hierarchy and naturalizing women's subjugation, its discussion being of primordial importance in the combat of sexual violence.